The Impact of Video-Based Drug Information on Medication Adherence among Hypertensive Patients : A Study at Dr. Sindhu Trisno Level-III Hospital Palu - Ririen Hardani; M. Fakhrul Hardani; M.Rinaldhi Tandah; Indah Ismiranti Awaliyah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Adherence of hypertensive patients in taking drugs is one of the determinants of the success of a treatment so that compliance can be influenced by the patient's knowledge and attitude in treating the disease. Objective: The purpose of this study was to determine the effect of providing education through video media on the level of knowledge, attitude, and adherence to taking medication for hypertensive patients at Dr. Sindhu Trisno Hospital Palu. Method: The method used in this study was quasi-experimental with pre-test and post-test approaches using questionnaires on outpatient hypertensive patients at Dr. Sindhu Trisno Hospital. Result: There are differences in knowledge, attitudes, and compliance of hypertensive patients before and after being given drug information with video media with a significance value of 0.000 < 0.05. The partial relationship for significance value attitude is 0.359 > 0.05, knowledge significance value is 0.906 > 0.05, and duration of treatment significance value is 0.882 > 0.05. Knowledge and attitude simultaneously significance value 0.441 > 0.05 Conclusion: It can be concluded that there is an influence of providing drug information with video media on the knowledge, attitudes, and compliance of hypertensive patients.